1985
DOI: 10.1111/j.1440-1827.1985.tb00612.x
|View full text |Cite
|
Sign up to set email alerts
|

LYMPHOMATOID GRANULOMATOSIS: Light Microscopic, Electron Microscopic and Immunohistochemical Study

Abstract: A case of lymphomatoid granulomatosis (LYG) involving the lungs, skin, stomach, and possibly the left kidney in a 60‐year‐old man is presented. The infiltrates in the lungs, stomach, and skin showed a polymorphic appearance, and consisted predominantly of lymphocytes of mature and blastic form and of a few neutrophils, plasma cells, and histiocytes. Most lymphoid cells showed irregularly shaped nuclei and clustered dense bodies, characteristics indicative of T lymphocytes. An immunohistochemical study confirme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1987
1987
1994
1994

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…T cells with helper/inducer phenotype predominate [7][8][9][10], and the clonal rearrangement of the T cell receptor (3-chain supports the hypothesis that LG may be correlated with lymphoproliférative T cell disorders [ 11,12].…”
Section: Introductionmentioning
confidence: 88%
“…T cells with helper/inducer phenotype predominate [7][8][9][10], and the clonal rearrangement of the T cell receptor (3-chain supports the hypothesis that LG may be correlated with lymphoproliférative T cell disorders [ 11,12].…”
Section: Introductionmentioning
confidence: 88%
“…Presently, it has been shown that many cases of LYG represent a proliferation of T lymphocytes, which might explain its propensity for extranodal involvement and peculiar histologic features of angioinvasion and granuloma formation. 214,15 It has also become evident that lymphoproliferation with angioinvasion in the lung and elsewhere can express a range of morphologic atypia, such as in the case of lymphomas of nodal origin, with identifiable low and high subsets. Three responses can be identified and they correlate well with the clinical outcome: BLAG (low grade), LYG (intermediate to high grade), large cell angiocentric lymphoma (high grade).…”
Section: Benign Lymphocytic Angiitis and Granulomatosismentioning
confidence: 99%
“…In the present case lym phohistiocytic infiltrates were composed almost entirely of T lymphocytes as deter mined by monoclonal antibodies. Today, based on immunocytochemical investiga tions [6][7][8][9][10][11][12], LYG is generally considered to be a true malignant lymphoma of T lym phocyte origin. However, a few reports have indicated a B cell origin [22][23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…To date more than 200 cases have been reported in the special references to its pulmonary involvement [2]. However it has recently been established that the disease should be considered to be a malignant lym phoma [3][4][5] of T lymphocyte origin by means of the investigations using the monoclonal antibodies to lymphocyte sub populations [6][7][8][9][10][11][12], Of particular sig nificance for dermatologists is the high inci dence of skin lesions in this disease and the fact that the cutaneous lesion may be the first sign of LYG occasionally [1,[13][14][15][16]. We report here a patient who had necrobiosislipoidica-like skin lesions as one of the first manifestations of LYG.…”
Section: Introductionmentioning
confidence: 99%